A SIMPLIFIED HYBRID METHODOLOGY FOR DESIGNING CORELESS AXIAL FLUX MACHINES - Pranjić , Franjo; Virtič, Peter (Journal of Energy Technology, 2024)
Axial flux permanent magnet generators (AFPMG) are used in many high torque applications, including wind generators. There are many design methodologies for AFPMG that are connected to simpledesign equations used for preliminary design. Analytical methods offer a fast preview of torque production of the designed machine with a certain degree of accuracy. The finite element method (FEM)is a more accurate numerical method than other methods and requires a great deal of time for simulations in the design procedure. This article presents a method for the design and analysis of an axialflux permanent magnet generator by using approximation polynomials.